2008
DOI: 10.1177/1358863x07084729
|View full text |Cite
|
Sign up to set email alerts
|

Atypical ischemic lower extremity ulcerations: a differential diagnosis

Abstract: Severe peripheral artery disease (PAD) is the predominant cause of ischemic ulcerations involving the lower extremities. PAD-associated ulcerations are typically distally located involving the feet, toes, and sometimes the calves. In contradistinction, atypical ischemic ulcerations of the lower extremity are often nonatherosclerotic in etiology, involve the proximal leg (thigh/buttocks), can evolve despite palpable distal pulses, and may coexist with other cutaneous aberrations (e.g. macules, purpura, nodules,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
(34 reference statements)
0
15
0
2
Order By: Relevance
“…A study from a tertiary referral center in Switzerland showed that 16 (52%) of 31 hypertensive ischemic leg ulcers were referred with a suspected diagnosis of PG [55]. However, there is a paucity of data in the literature pertaining to the differential diagnosis between PPG and parastomal ischemia-related skin ulcers, probably due to the fact that the abdominal wall is an uncommon location for ischemic changes [56]. …”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%
“…A study from a tertiary referral center in Switzerland showed that 16 (52%) of 31 hypertensive ischemic leg ulcers were referred with a suspected diagnosis of PG [55]. However, there is a paucity of data in the literature pertaining to the differential diagnosis between PPG and parastomal ischemia-related skin ulcers, probably due to the fact that the abdominal wall is an uncommon location for ischemic changes [56]. …”
Section: Diagnosis and Differential Diagnosismentioning
confidence: 99%
“…Calciphylaxis occurs mainly in patients with kidney disease, and biopsy shows calcium deposition within arterioles and venules and subcutaneous tissues. 32 In diabetic ulcers, mediasclerosis can be demonstrated in about 30% of patients. 33 Of the 40 patients described by Schnier et al, only 35% did not have signs of arteriosclerosis or CVI.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…It has long been understood that the development of nonatherosclerotic PVD, with its implicit failure of appropriate matching of blood perfusion to meet requisite metabolic demand, is associated with a severely compromised ability of the skeletal muscle to maintain performance (i.e., developed tension levels) (19,44). However, with the use of the OZR model of the metabolic syndrome, it has been clearly demonstrated that blood-perfused skeletal muscle rates of fatigue are increased as compared with LZR and that this compromised performance is not simply a function of global ischemia (25).…”
Section: Discussionmentioning
confidence: 99%
“…Although underrepresented to date, this is an exceedingly important area of investigation, since a growing body of evidence suggests that an increasing number of human subjects are afflicted with the symptomology of PVD in the absence of overt plaque/lesion development (12,19,31,44,45).…”
mentioning
confidence: 99%